2011
DOI: 10.1074/jbc.c110.212589
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Sequesters Dnmt1 from the Nucleus

Abstract: DNA methylation is a major epigenetic modification that regulates gene expression. Dnmt1, the maintenance DNA methylation enzyme, is abundantly expressed in the adult brain and is mainly located in the nuclear compartment, where it has access to chromatin. Hypomethylation of CpG islands at intron 1 of the SNCA gene has recently been reported to result in overexpression of ␣-synuclein in Parkinson disease (PD) and related disorders. We therefore investigated the mechanisms underlying altered DNA methylation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(177 citation statements)
references
References 19 publications
7
157
2
2
Order By: Relevance
“…Matsumoto et al 2010) only found alterations of the methylation state in the SN, but not CG or putamen. Moreover, a third study described reduced methylation levels using methylation-specific PCR (MSP) and an antibody against 5-methylcytosine (5-mC) in samples of the frontal cortex (FC) together with decreased expressions of DNA (cytosine-5)-methyltransferase 1 (DNMT1) and an inverse correlation with oligomerization of SNCA (Desplats et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Matsumoto et al 2010) only found alterations of the methylation state in the SN, but not CG or putamen. Moreover, a third study described reduced methylation levels using methylation-specific PCR (MSP) and an antibody against 5-methylcytosine (5-mC) in samples of the frontal cortex (FC) together with decreased expressions of DNA (cytosine-5)-methyltransferase 1 (DNMT1) and an inverse correlation with oligomerization of SNCA (Desplats et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The concept of ectopic localization of epigenetic (and other) molecules in a variety of situations is not unique to the present findings. Many studies have demonstrated reduced epigenetic molecules in the nucleus in a variety of situations, for example (Desplats et al, 2011; Kamikawa and Donohoe, 2014; Mastroeni et al, 2009; Ogawa et al, 2003; Thatcher and LaSalle, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work has been conducted by Desplats et al (2011) describing an interaction between SCNA and DNMT1 (methylation maintenance) that likely contributes to the broader hypomethylation shifts in neurons of PD patients. Shifts in DNA methylation are a definite component of PD.…”
Section: Resultsmentioning
confidence: 99%